PENGARUH INSIGHT SOSIAL MEDIA INSTAGRAM TERHADAP PENJUALAN PT INFIA NIAGA DIGITAL - Pramudita, Aditia Sovia (JURISMA : Jurnal Riset Bisnis & Manajemen, 2020)
Information communication technology advances is affected lifestyle changes in Indonesia. The advancement of social media and ecommerce changes retail to digital which is also very noticeable nowadays. Referring to Promotion Mix, promotion made to increase sales on Instagram by PT Infia Niaga Digital is divided into campaign content (Promotion sales) and product content (advertising). The purpose of this research is to measure the correlation of campaign content and product content to sales at PT Infia Niaga Digital. This study uses multiple Linear regression where there are two or more x variables that affect Y. The variables used in this study are insights on Instagram such as likes, comments and impression as x variables with Y is Sales. By using the SPSS application, the results obtained from this research are promotion on Instagram with marketing mix i.e. campaign content does not affect sales with 3.4% influence simultaneously while product content also Has no effect on sales and affects 7.7% of sales simultaneously.